Analisis Pemilihan Dukun sebagai Penolong Persalinan (Studi Kasus di Puskesmas Bulak Banteng, Kota Surabaya) - Nurul Habibah Umar (Jurnal Manajemen Kesehatan Indonesia, 2019)
Maternal mortality of Surabaya, in 2017, reached 79.40 per 100,000 live births due to direct causes by 77.2%. There are many programs to reduce maternal mortality and infant mortality such as improving delivery services in the health facility. In 2008, the partnership program between midwives and traditional birth attendants had developed to increase the access of quality maternal services for mothers and babies. However, in 2017 the delivery practice with traditional birth attendants has remained active in the area of Bulak Banteng Community Health Center, Surabaya.      This study aimed to analyze the women’s decision selecting the traditional birth attendants for their delivery practice by exploring knowledge factor, belief factor, health service access factor, and family factor in Bulak Banteng Community Health Center of Surabaya. The research was a qualitative study using the approach of case study including in-depth interview and exploring secondary data. The sample was the mothers who delivered the baby with the traditional birth attendant from a previous year ago, and the midwife of health community center. The variable from this study were knowledge factor, belief factor, health service access factor, and family factor. The study used the analytical method consisted of data collecting, data reduction, and verification.      The result showed less knowledge factor of healthy and safe delivery in the community. The belief factor and family factor held an important role in the selection of the traditional birth attendants during birth attendance, while the factor of health service access showed nothing related to the selection process. There is a need to implement health education for pregnant women, husband, family, and people with an aim of giving the understanding about healthy and safe birth attendance. In conclude, the selection on traditional birth attendant was influenced by knowledge factor, belief factor, and family factor.